Book Review. Cultural Heritage in a Changing World - Ashika Prajnya Paramita (Humaniora, 2016)
Edited by Karol Jan Borowiecki, Neil Forbes, and Antonella Fresa, this collection of essays was developed within the RICHES Project to address the issues surrounding cultural heritage in the era of digital technologies. The 21st century has witnessed rapid developments in digital technologies that have led to major changes in all aspects of society. This book aims to reflect the relationship between cultural heritage and these changes. Written by experts from various background, this book implements an interdisciplinary approach its observations, and provides a comprehensive view of the changes that occur in the society. In various perspectives, the collection show how cultural heritage, mainly in Europe, should be preserved through digital availability and accessibility.